Bagaimana Respon Siswa terhadap E-Modul Matematika dengan Konteks Budaya Sumatera Selatan? - Hartatiana, Hartatiana; Wardani, Ambarsari Kusuma (SJME (Supremum Journal of Mathematics Education), 2024)
This research explores the utilization of an e-module with the context of local wisdom from South Sumatra in mathematics education at the junior high school level. Involving ninth-grade students from four different schools in South Sumatra, the study aims to evaluate students' responses to the e-module. The research methodology includes One-to-one and small group stages, focusing on clarity, user-friendliness, and students' interest in the e-module content. The findings indicate that students responded positively to the e-module, expressing high enthusiasm for multimedia features such as images, videos, and interactive exercises. The diversity of multimedia elements aids in visually and contextually explaining mathematical concepts, making learning more engaging. The flexibility of the e-module allows students to learn independently anywhere and anytime, overcoming constraints of space and time in traditional learning settings. The integration of local wisdom is recognized as an added value, providing students with additional insights into the culture of South Sumatra. So it can be concluded that the use of e-modules in the context of local wisdom from South Sumatra has a positive impact on mathematics learning at junior high school level.